2015
DOI: 10.1038/srep10223
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance enterographic predictors of one-year outcome in ileal and ileocolonic Crohn’s disease treated with anti-tumor necrosis factor antibodies

Abstract: The aim of the study was to assess the role of magnetic resonance enterography (MRE) in predicting one-year efficacy of anti-tumor necrosis factor antibodies - infliximab (IFX), adalimumab (ADA) in Crohn’s disease (CD) patients primarily responding to therapy. We performed retrospective analysis among 61 CD patients who had undergone a successful IFX/ADA induction therapy and were treated with maintenance doses. All patients underwent MRE at week 0. We assessed which MRE features were predictive for steroid-fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…The mucosa overlying established Crohn’s disease strictures has a pro-fibrotic pattern of gene expression. 24 Whether ileal gene signatures would reveal these processes at an uncomplicated stage of disease was unknown. We detected a pronounced extracellular matrix gene signature in patients who ultimately progressed to strictures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mucosa overlying established Crohn’s disease strictures has a pro-fibrotic pattern of gene expression. 24 Whether ileal gene signatures would reveal these processes at an uncomplicated stage of disease was unknown. We detected a pronounced extracellular matrix gene signature in patients who ultimately progressed to strictures.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the possible underestimation of children with early fibrosis at diagnosis could explain why anti-TNFα therapy did not affect progression to stricturing. 24,29 Most participants had endoscopic ileal inflammation and so biopsies were taken from inflamed tissue. However, we were not able to obtain ileal biopsies from inflamed and non-inflamed segments in the same patients, and so cannot directly address the degree to which acute inflammation affected the gene signatures.…”
Section: Discussionmentioning
confidence: 99%
“…Other MRI evaluations, such as mucosal ulcer and ADC value, were used in recent studies[ 22 ]. Some studies[ 23 - 27 ] focused on the accuracy of MRI indicators for the evaluation of CD and the response to medical therapy. One study reported that changes in CD clinical activity were significantly correlated with changes in MRI activity score[ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite apparent symptom resolution, an active disease process often continues, accruing irreversible damage over time [6]. Advanced body-imaging techniques such as magnetic resonance enterography (MRE) and computed tomography enterography (CTE) allow detailed assessment of structural changes incurred as a result of the ongoing disease process (e.g., mucosal enhancement, bowel wall thickness) [7]. The Lémann index (Li) is a recently introduced objective quantitative measure of CBD based on small bowel imaging, upper endoscopy, perianal assessment, and colonoscopy [8,9].…”
Section: Introductionmentioning
confidence: 99%